2015
DOI: 10.3892/mmr.2015.4585
|View full text |Cite
|
Sign up to set email alerts
|

SNAIL transcription factor increases the motility and invasive capacity of prostate cancer cells

Abstract: The incidence and mortality rates of prostate cancer (PCa) are increasing, and PCa is almost the second-leading cause of cancer-associated mortality in men. During tumor progression, epithelial cells decrease the number of adhesion molecules, change their polarity and position, rearrange their cytoskeleton and increase their migratory and invasive capacities. These changes are known under the concept of epithelial-mesenchymal transition (EMT). EMT is characterized by an upregulation of certain transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…An important characteristic of EMT is the loss of expression of epithelial cell markers and the development of a mesenchymal phenotype by increasing mesenchymal markers, such as snail1, snail2, and α‐SMA . Recently, several studies have indicated that EMT progression is regulated by activation of snail signaling in various cancer cell lines including prostate and breast cancer cells . We showed above that inflammatory mediators, such as CCL2, IL‐6, CXCL8, and PGE2, produced by Tv stimulation of prostate epithelial cells induced EMT of PCa cells through the receptors of these inflammatory mediators.…”
Section: Discussionmentioning
confidence: 70%
“…An important characteristic of EMT is the loss of expression of epithelial cell markers and the development of a mesenchymal phenotype by increasing mesenchymal markers, such as snail1, snail2, and α‐SMA . Recently, several studies have indicated that EMT progression is regulated by activation of snail signaling in various cancer cell lines including prostate and breast cancer cells . We showed above that inflammatory mediators, such as CCL2, IL‐6, CXCL8, and PGE2, produced by Tv stimulation of prostate epithelial cells induced EMT of PCa cells through the receptors of these inflammatory mediators.…”
Section: Discussionmentioning
confidence: 70%
“…Among them, Snail1 and Snail2 are activated in the EMT during development, fibrosis, and cancer. The upregulation of Snail1 is found in many different types of cancer such as gastric, colorectal, and prostate cancer . In addition, the overexpression of Snail1 enhanced the motility and invasion of prostate cancer cells, and the silencing of Snail remarkedly suppressed the adhesion, migration, and invasion of Hep‐2 cells .…”
Section: Small Molecules Against Emtmentioning
confidence: 93%
“…Recently, it was reported that toosendanin significantly inhibited TGF‐β1‐induced EMT in lung cancer cells via the extracellular signal‐regulated kinase (ERK)/Snail pathway and suppressed EMT and tumor growth in pancreatic cancer by deactivating the RAC‐α serine/threonine‐protein kinase (Akt)/mechanistic target of rapamycin (mTOR) pathway (Figure ), which suggests that toosendanin is a promising pharmacological agent for the treatment of cancer . A recent study revealed that neferine enhanced oxaliplatin sensitivity by inhibiting EMT via the Snail pathway . In addition, ponicidin is a major diterpenoid compound extracted from Rabdosia rubescens (Hemsl.)…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
See 2 more Smart Citations